Mice lacking ASIC2 and βENaC are protected from high-fat-diet-induced metabolic syndrome - Hamby, Madison; Stec, David E.; Hildebrandt, Emily; Stec, Donald F.; Drummond, Heather A. (Frontiers in Endocrinology, 2024)
Degenerin proteins, such as βENaC and ASIC2, have been implicated in cardiovascular function. However, their role in metabolic syndrome have not been studied. To begin to assess this interaction, we evaluated the impact of a high fat diet (HFD) on mice lacking normal levels of ASIC2 (ASIC2 -/-) and βENaC (βENaC m/m ). Twenty-week-old male and female mice were placed on a 60% HFD for 12 weeks. Body weight was measured weekly, and body composition by non-invasive ECHO MRI and fasting blood glucose were measured at 0, 4, 8 and 12 weeks. A glucose tolerance test was administered after 12 weeks. Differences between ASIC2 -/-/βENaC m/m and WT groups were compared using independent t-tests or ANOVA where appropriate within each sex. Data are presented as mean ± SEM and ASIC2 -/-/βENaC m/m vs. WT. At 20 weeks of age, ASIC2 -/-/βENaC m/m mice (n=9F/10M) weighed less and gained less weight than WT (n=12F/16M). Total body fat and lean body masses were reduced in female and male ASIC2 -/-/βENaC m/m mice. Total body fat and lean body masses as % control were identical at the end of 12 weeks. Fasting blood glucoses were lower in female and male ASIC2 -/- /βENaC m/m vs. WT mice after 12 weeks HFD. The area under the curve for the glucose tolerance test was reduced in female and tended (p=.079) to decrease in male ASIC2 -/-/βENaC m/m . Plasma leptin and insulin were reduced in female and male ASIC2 -/-/βENaC m/m vs. WT mice. Plasma insulin in female ASIC2 -/-/βENaC m/m mice remained unchanged throughout the HFD period. Liver and liver fat masses, as well as percent liver fat, were reduced in both female and male ASIC2 -/-/βENaC m/m mice after HFD. Plasma triglycerides, cholesterol, LDL-and HDL-cholesterols were markedly improved in male and/or female ASIC2 -/-/βENaC m/m following the HFD. These novel findings suggest that loss of ASIC2 and βENaC offer a significant protection against HFD-induced metabolic syndrome.